CULTIVATING ISLAMIC ECONOMIC VALUES AND GENEROUS CHARACTER IN TPQ CHILDREN THROUGH ISLAMIC STORIES AND INTERACTIVE EDUCATION IN TAWANG VILLAGE - Ghulam Halim Mahmud; Saifudin Saifudin (Penelitian dan Pengembangan Ilmu, 2025)
Islamic economic education has a strategic role in shaping the social and spiritual character of children from an early age, especially through the introduction of the value of zakat, infaq and sadaqah. However, the learning methods in many TPQs are still rote and have not touched on the applicative aspects. This service activity aims to instill Islamic economic values and generous characters to TPQ children in Tawang Hamlet through the method of Islamic stories and interactive education. This activity uses an educational-participatory approach through storytelling activities, discussions, and direct sharing practices. The pre-test and post-test results showed an increase in children's understanding and generous attitudes by an average of 41.5%, with the highest increase in the aspect of sharing practices by 46.2%. This finding shows that a fun contextual approach can improve Islamic economic literacy while shaping positive social behavior in early childhood. This program can be used as an alternative learning model that is relevant to the TPQ curriculum and replicated in other areas to form a religious, caring and civilized generation.